Research on Assembling Steel Tower on The Top of Skyscraper by Gradual Erection - Dr. Ik Jun Won; Chol Su Ryu (Talenta Publisher, 2023)
The top surface of the hise rise buildings are very small for working space. The findings of this research is to clarify the scientific and technological problems to assemble big steel tower in different shapes on the top of the skyscrapers to the height of dozens of meters safely by using simple mechanical equipment including hoist, hydraulic jack by gradual erection method.